(untitled) (Nativa, 2025)
This study investigates the impact of various fertilization methods on the growth, yield, and phytochemical composition of Atherolepis pierrei Costantin, a medicinal plant with significant pharmaceutical potential. The experiment examined the effects of organic and chemical fertilizers, including vermicompost, poultry manure, and NPK fertilizers, on plant development and the production of bioactive compounds. Findings reveal that combined fertilization strategies, particularly those involving moderate levels of compost and NPK, optimized plant growth, yield, and biomass accumulation. Phytochemical analysis using Gas Chromatography-Mass Spectrometry (GC-MS) identified several bioactive compounds such as benzaldehyde, 2-hydroxy-4-methoxy, lupeol, and β-amyrin, known for their antioxidant, antimicrobial, anti-inflammatory, and anticancer activities. The study highlights the role of tailored fertilization approaches in enhancing both the physical growth and medicinal potential of Atherolepis pierrei. These results underline the importance of integrated fertilization strategies for sustainable agricultural practices and the production of high-value medicinal plants. Further research is recommended to explore the full pharmacological potential of the identified bioactive compounds and refine fertilization methods for optimizing both crop yield and bioactive compound production. Keywords: fertilization methods; plant growth parameters; bioactive compounds; sustainable agriculture; medicinal plant utilization. Avaliação do crescimento e potencial farmacológico de Atherolepis pierrei Constantin por meio de fertilização sinérgica e análise de compostos bioativos RESUMO: Este estudo investiga o impacto de vários métodos de fertilização no crescimento, rendimento e composição fitoquímica de Atherolepis pierrei Constantin, uma planta medicinal com significativo potencial farmacêutico. O experimento analisou os efeitos de fertilizantes orgânicos e químicos, incluindo vermicomposto, esterco de aves e fertilizantes NPK, no desenvolvimento das plantas e na produção de compostos bioativos. Os resultados revelaram que as estratégias de fertilização combinada, particularmente aquelas envolvendo níveis moderados de composto e NPK, otimizaram o crescimento das plantas, o rendimento e a acumulação de biomassa. A análise fitoquímica utilizando Cromatografia Gasosa com Espectrometria de Massa (GC-MS) identificou vários compostos bioativos, como benzaldeído, 2-hidroxi-4-metoxil, lupeol e β-amirina, conhecidos por suas atividades antioxidante, antimicrobiana, anti-inflamatória e anticâncer. O estudo destaca o papel de abordagens de fertilização específicas na melhoria tanto do crescimento físico quanto do potencial medicinal de Atherolepis pierrei. Estes resultados ressaltam a importância de estratégias de fertilização integradas para práticas agrícolas sustentáveis e a produção de plantas medicinais de alto valor. Recomenda-se mais pesquisas para explorar o pleno potencial farmacológico dos compostos bioativos identificados e aprimorar os métodos de fertilização para otimizar tanto o rendimento das culturas quanto a produção de compostos bioativos. Palavras-chave: métodos de fertilização; parâmetros de crescimento das plantas; compostos bioativos; agricultura sustentável; utilização de plantas medicinais.